ENHANCING FIRST-GRADE STUDENTS’ VOCABULARY THROUGH CROSSWORD PUZZLES at SMP NEGERI UNGGULAN 1 PULAU MOROTAI - Jasmal Martora; Megawati Basri; Vemi Yong (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasifik Morotai, 2023)
This study aims to determine the effects of crossword puzzles on the First-Grade students’ vocabulary of SMP Negeri 1 Morotai Island in the academic year 2020/2021. This study employed a quantitative approach with a pre-experimental research design. Questionnaires and tests were used as research instruments for data collection purposes. 52 First-Grader students were randomly selected to participate in the research process upon which a pre-test, treatment, and post-test were conducted. The results showed that the average score obtained by students during the pre-test was 45.28. The researcher then applied the crossword puzzles during the treatment process to see their effects on the student’s vocabulary. When the post-test was conducted, the students' average scores significantly rose to 76.19. This increase was found across aspects of vocabulary such as nouns, spelling, pronunciation, and understanding of the contextual meaning of the vocabulary in sentences. Thus, it can be concluded that Crossword Puzzles increase the First-Grade Students’ vocabulary of SMP Negeri Unggulan Pulau Morotai.